Investigating the structure of herpes simplex virus - 1 at the interface between the capsid and tegument - Fan, Wan Ho (University of Glasgow, 2015)
The structure of the herpesviruses particle is characterised by an icosahedral capsid surrounded by a proteinaceous tegument layer and is enclosed by a lipid envelope. The understanding of the structure of the capsid, primarily through the use of cyro-electron microscopy, is greater to than of the tegument, due to the typically amorphous nature of the tegument. The interaction between the capsid and tegument has been well studied, unveiling interactions limited to the capsid vertices involving two minor capsid proteins, pUL17 and pUL25, and the large tegument protein pUL36. In herpes simplex virus – 1 (HSV-1), pUL17 and pUL25 form the capsid vertex-specific component (CVSC), a heterodimeric structure which resides in top of triplexes between peripentonal hexons. pUL36 has been suggested to connect the CVSC to the penton and to the rest of the tegument proteins. Recent studies on the gammaherpesvirus Karposi’s sarcoma-associated herpesvirus (KSHV) and the alphaherpesvirus pseudorabies virus (PrV) have questioned both the protein content of the CVSC and the organization of pUL17 and pUL25. As well as the composition of the CVSC, these studies have provided further insight as to the location of tegument assembly to the capsid, a subject that remains a highly contested. In order to clarify the content of the CVSC, virus mutants with deletions of the large inner tegument protein pUL36, and a second inner tegument protein, pUL37, were analysed using cryo-electron microscopy and icosahedral reconstructions. The examination and comparisons of these mutants with wild-type HSV-1 revealed that the CVSC is not only formed by pUL17 and pUL25 as originally reported, but also pUL36, as suggested in the most recent studies. In addition, comparisons of the capsid structure of the pUL36 deletion mutant with a mutant with a full deletion of pUL34, a protein implicated in nuclear egress as part of the nuclear envelopment complex (NEC) and therefore cannot exit the nucleus, suggest that at least part of pUL36 is present on nuclear capsids. Further analyses of the mutant virus with pUL36 deleted using immunofluorescence and Western blotting, along with the capsid reconstruction of a pUL36 deletion mutant which retains only the N-terminal 361 codons suggest that the C-terminal end of pUL36 is present in the nucleus. The work presented here offers additional evidence to clarify the roles of pUL17, pUL25 and pUL36 in tegument assembly. In particular, structural analysis has implied that the contributions of pUL36 to the nuclear capsid stabilizes the CVSC structure from a structural stand-point, emphasizing it’s importance as a multifunctioning protein which acts as a bridge between the capsid and tegument.